2010
DOI: 10.1245/s10434-010-0999-y
|View full text |Cite
|
Sign up to set email alerts
|

Improved Results of a Surgical Resection for the Recurrence of Hepatocellular Carcinoma After Living Donor Liver Transplantation

Abstract: Surgical therapy might be useful for patients who experience a recurrence of HCC after LDLT to improve their outcome, when such treatment is available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 25 publications
2
49
0
Order By: Relevance
“…In the present study, all patients were under immunosuppression after LT. The immunosuppression might have some effects on prognosis (21) and miRNA expression. Our present study revealed that miR-18a regulates the levels of TNFAIP3 in HCC, which is known to be decreased in HCC and associated with early intrahepatic recurrence after hepatic resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, all patients were under immunosuppression after LT. The immunosuppression might have some effects on prognosis (21) and miRNA expression. Our present study revealed that miR-18a regulates the levels of TNFAIP3 in HCC, which is known to be decreased in HCC and associated with early intrahepatic recurrence after hepatic resection.…”
Section: Discussionmentioning
confidence: 99%
“…(21) The RNA samples from 3 patients who underwent resection of recurrences after LDLT were made available for miRNA microarray analysis. The 3 patients included a man (patient 1) with peritoneal recurrence and infected by hepatitis B virus (HBV), and a woman (patient 2) and a man (patient 3) with lung recurrences and hepatitis C virus (HCV) infection.…”
Section: Microrna Microarray Analysismentioning
confidence: 99%
“…In fact, the Kyushu University group in 2010 reported 17 patients with HCC recurrence limited to the liver after transplantation; 9 of these patients were treated surgically and experienced survival approximating that of patients who did not experience HCC recurrence. 9 All major series of HCC recurrence have substantiated the better survival of patients treated with resection; there is, however, an obvious case selection bias, so it is impossible to determine the extent to which surgery rather than favorable biology explains the difference. There is indirect evidence for a tumor biology explanation: vascular invasion was found during the original explant pathology examination in only 3 of 7 patients with surgically resectable recurrence but in all 9 patients whose recurrence pattern was unsuitable for surgery in 1 study.…”
Section: Resection/radiofrequency Ablationmentioning
confidence: 99%
“…According to many articles (73)(74)(75)(76)(77)(78), time elapsed since LT and the appearance of recurrence is an important prognostic factor regarding survival, with worst prognosis expected with early HCC recurrence (within 24 months). Early HCC recurrence could be due to non-detectable extra-hepatic spread that was found before performing liver transplantation, and also as a consequence of circulating HCC cell clones engrafting and growing in a target organ in the post-transplant period (79).…”
Section: Local Recurrence After Liver Transplantationmentioning
confidence: 99%